THE ESTIMATION ACCURACY OF LIVE WEIGHT FROM METRIC BODY MEASUREMENTS IN ONGOLE GRADE COWS - Paputungan, U.; Hakim, L.; Ciptadi, G.; Lapian, H.F.N. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
length in North Sulawesi province. Data on animal live weight (LW), body length (BL) and chest girth(CG) were collected from all cows (n=363) kept by traditional household farmers. Regression analysiswas carried out to estimate LW from all linear body measurements. Data were classified based on age ofanimals consisted of five groups with the first age group of two and half years old, to the fifth age groupof seven and half years old. The results showed that age significantly (P<0.05) influenced all bodymeasurements. Correlations between all pairs of measurements were highly significant (P<0.001) for allage groups. Regression analysis showed that live weight could be predicted accurately from chest girthand body length (R2=0.97). Multiple regression model can be recommended to predict live weight ofOngole grade cows based on those variables with their age groups ranging from 2.5 to ≥7.5 years old asfollows: Live weight (kg) = -806.410 + 4.79835 CG (cm) + 2.83500 BL (cm).